6(6-6p)=36+5p

Simple and best practice solution for 6(6-6p)=36+5p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(6-6p)=36+5p equation:


Simplifying
6(6 + -6p) = 36 + 5p
(6 * 6 + -6p * 6) = 36 + 5p
(36 + -36p) = 36 + 5p

Add '-36' to each side of the equation.
36 + -36 + -36p = 36 + -36 + 5p

Combine like terms: 36 + -36 = 0
0 + -36p = 36 + -36 + 5p
-36p = 36 + -36 + 5p

Combine like terms: 36 + -36 = 0
-36p = 0 + 5p
-36p = 5p

Solving
-36p = 5p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-5p' to each side of the equation.
-36p + -5p = 5p + -5p

Combine like terms: -36p + -5p = -41p
-41p = 5p + -5p

Combine like terms: 5p + -5p = 0
-41p = 0

Divide each side by '-41'.
p = 0

Simplifying
p = 0

See similar equations:

| x^6-5x^4+4x^2+x+8=0 | | 2z=4z-2 | | -4(3+a)-6(1-a)=-8 | | -12=4(w-5)-6w | | -4(3+a)-6(1-a)=8 | | 32=28y+0 | | 12t^3-9t^2+28t=3t^2(4t-3)+7(4t-3) | | 13x+42=4x+5 | | 6y+1.5x=8 | | 2(x-3)+2=4(x+6)-30 | | -2+2p=-14 | | 13y+(4y)(3x)+x= | | 5x+15=15-3x+9 | | 4y-6=-22 | | 2(x-4)+3=4x+7 | | 6x^2+47x+92=0 | | (2x+28)=(3x+137) | | -24-7n=-8(3-6n) | | 42=3(2-3n)-6 | | -19=3(7+3n)+8(8n-5) | | 180=111-u | | -12+19/-7= | | -12+-42/-7= | | 60x^2-20x+1=0 | | 84=2w+2L-3 | | 15y-11y=20 | | -12+-126/-7= | | x^2+(x*y)=120 | | 84+3x=1x | | -9u-5+6=19 | | -12+h/7=6 | | -a+5+6a=1+5a+3 |

Equations solver categories